Media Pengembangan Dakwah Kultural dalam Aktitas LESBUMI Nahdlatul Ulama’ Kecamatan Patebon - Widy Febriani; Nur Shofa’ati (Jurnal Al-Hikmah, 2022)
Art and culture is one of the traditional legacies that must be preserved as a feature of Indonesia's diversity. Culture itself can be called the whole of human life which includes art, morals, customs, laws and all other aspects that are normative. The Indonesian Muslim Cultural Artists Institute (Lesbumi) is an institution that operates under the auspices of the Nahdlatul Ulama (NU), founded on March 28, 1962 in Bandung. This article intends to provide an overview of the activities of the institution which is understood as one of the bridges of cultural da'wah, namely by using the media of art, culture and community traditions. Remember, Lesbumi is developing Islamic arts, such as: music, Islamic theatre, literature and film. Always placed as a forum for Muslim artists and humanists Nahdlatul Ulama'. Meanwhile, Lesbumi adheres to the Ahlusunnah wal jamaah fil madhahibil arbah principle, which is ukhuwah Islamiyah in nature, and its goal is to serve Islamic ideals and teachings, by exploring elements of Islamic art and culture.